2022
DOI: 10.1039/d1sc06807e
|View full text |Cite
|
Sign up to set email alerts
|

An asymmetric 2,3-fluoranthene imide building block for regioregular semiconductors with aggregation-induced emission properties

Abstract: A new electron-deficient 2,3-fluoranthene imide unit was easily synthesized through a one-pot reaction for constructing small molecule regioregular semiconductors with good carrier transport ability and strong solid-state emission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…4). 98 All fluoranthenefused imides developed in this study were shown to exhibit aggregation-induced emission, with compound 134a having the highest photoluminescence quantum yield (5.9%) in the solid state as a powder. Interestingly, compound 134a was found to behave as a p-type semiconductor, whereas the introduction of fluorines into the thiophene ring in 134b switches its behaviour into an n-type semiconductor.…”
Section: Selected Applications Of Fluoranthenesmentioning
confidence: 81%
“…4). 98 All fluoranthenefused imides developed in this study were shown to exhibit aggregation-induced emission, with compound 134a having the highest photoluminescence quantum yield (5.9%) in the solid state as a powder. Interestingly, compound 134a was found to behave as a p-type semiconductor, whereas the introduction of fluorines into the thiophene ring in 134b switches its behaviour into an n-type semiconductor.…”
Section: Selected Applications Of Fluoranthenesmentioning
confidence: 81%
“…[42,28] We previously designed and synthesized a novel acceptor unit, i.e., 2,3-fluoranthene imide, and used it to develop a series of new p-type semiconductors. [43] We then assumed 4) to afford BTF14. The molecular structures were well confirmed by NMR and high-resolution mass analysis.…”
Section: Resultsmentioning
confidence: 99%
“…[ 42,28 ] We previously designed and synthesized a novel acceptor unit, i.e., 2,3‐fluoranthene imide, and used it to develop a series of new p ‐type semiconductors. [ 43 ] We then assumed that 2,3‐imide fluoranthene could be also a promising building block to construct interlayer materials for NiO x ‐based PSCs. In this context, we designed and synthesized a new D–A type semiconductor (BTF14, Figure 1b) using 2,3‐fluoranthene imide as the acceptor unit and triphenylamine as the donor unit, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it shows attractive electron‐deficient feature because of the cyclopentene‐fused nonalternant structure. [ 57–59 ] Currently, fluoranthene‐based building blocks have been widely used for constructing organic semiconductors. [ 60–63 ] Among them diazabenzo[ k ]fluoranthene derivatives have attracted particular interests as a type of efficient A units for constructing NFAs and thermally activated delayed fluorescence emitters.…”
Section: Introductionmentioning
confidence: 99%